The Effect of Intellectual Capital and Sustainability Report Disclosure on Firm Value : (Study on the Food and Beverage Sector for the Period 2022-2024) - Iklima Abdul Halid; Nilawaty Yusuf; Mentari Rizki Sawitri Pilomonu (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to examine the effects of intellectual capital and sustainability report disclosure on firm value among food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2022-2024 period. Employing a quantitative appoarch, the study uses secondary data collected from corporate finansial statements and sustainability reports. The data analysis technique is panel data regression. The sample consists of 30 food and beverage sub-sector companies for the 2022-2024 period, seceted using a purposive sampling method based on spesific criteria to ensure data relevance and representativeness. The results indicate that: (1) intellectual capital, measured using the Value Added Intellectual Capital (VAIC), has no significant effect on firm value; (2) sustainability report disclosure, measured using the Sustainability Report Disclosure Index (SRDI), also has no significant effect on firm value; and (3) simultaneously intellectual capital and sustainability report disclosure do not aaffect firm value. The coefficient of determination (R2) is 2,54%, indicating the model has low explanatory power for variations in firm value, while the remaining 97,46% is explained by variables outside the model.